2019
DOI: 10.21511/bbs.14(3).2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Performance of deposit money banks and liquidity management in Nigeria

Abstract: This study examined the performance of selected quoted deposit banks of Nigeria and liquidity management. Secondary data used was extracted from the financial statements of 15 money deposit banks out of population of 17 deposit money banks on the Nigerian Stock Exchange (NSE) for 2012–2017 (six years). The descriptive research design was used. The data collected was analyzed using ordinary least square method (OLS). Liquidity management was measured using capital ratio (CTR), current ratio (CR) and cash ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Profitability is used in this study as a proxy for measuring company financial performance, similar to earlier studies. (Otekunrin et al, 2019;Otekunrin et al, 2020;Otekunrin et al, 2023). Numerous financial measures, such as return on equity (ROE) and return on sales (ROS), can be used to assess a company's profitability.…”
Section: Firm Performancementioning
confidence: 99%
“…Profitability is used in this study as a proxy for measuring company financial performance, similar to earlier studies. (Otekunrin et al, 2019;Otekunrin et al, 2020;Otekunrin et al, 2023). Numerous financial measures, such as return on equity (ROE) and return on sales (ROS), can be used to assess a company's profitability.…”
Section: Firm Performancementioning
confidence: 99%
“…Pada penelitian sebelumnya ada beberapa hasil penelitian yang menunjukkan inkonsistensi seperti penelitian oleh membuktikan jika kecukupan modal mampu dipengaruhi oleh kualitas aset namun membuktikan sebaliknyab [4], [5]. Penelitian oleh membuktikan jika likuiditas berpengaruh pada kecukupan modal namun penelitian lain membuktikan sebaliknya [6], [7].…”
Section: Pendahuluanunclassified
“…Performance has been measured using indicators such as profitability, market share and sales volume (Ogbuji & Zorbari-Nwitambu, 2017;Zorbari-Nwitambu, 2017). Otekunrin et al (2019) and Molyneux and Thornton (1992) in separate studies have maintained that the most viable measures of bank performance include return on assets (ROA) and return on equity (ROE). A study conducted by Flamini, McDonald, and Schumacher (2009) revealed that bank profits are high in Sub-Saharan Africa compared to other regions.…”
Section: Bank Performancementioning
confidence: 99%